2020
DOI: 10.1017/s0007114520003268
|View full text |Cite
|
Sign up to set email alerts
|

The effect of soya consumption on inflammatory biomarkers: a systematic review and meta-analysis of clinical trials

Abstract: Inflammation is a major cause of chronic diseases. Several studies have investigated the effects of soy intake on inflammatory biomarkers; however, the results are equivocal. The aim of this study was to conduct a systematic review and meta-analysis of clinical trials that evaluated the effect of soy consumption on inflammatory biomarkers. Medline, Scopus, ISI Web of Science, and Google Scholar were systematically searched, up to and including May 2020, for clinical trials that evaluated the effects of soy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…Additionally, experimental studies have not observed a significant effect of soy food consumption on serum CRP levels (74) that may be attributed to the interaction of multiple nutrients contained in whole soy foods (75) compared with isolated sources (76) . Our analysis revealed a significant effect of soy protein supplementation in reducing serum TNF-α levels, which are in line with previous research (77,78) , although, insignificant reductions of serum IL-6 levels were displayed as reported previously (23) . Furthermore, subgroup analysis showed that the addition of isoflavones did not decrease serum CRP and IL-6 levels; however a significant reduction of serum TNF-α was observed.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, experimental studies have not observed a significant effect of soy food consumption on serum CRP levels (74) that may be attributed to the interaction of multiple nutrients contained in whole soy foods (75) compared with isolated sources (76) . Our analysis revealed a significant effect of soy protein supplementation in reducing serum TNF-α levels, which are in line with previous research (77,78) , although, insignificant reductions of serum IL-6 levels were displayed as reported previously (23) . Furthermore, subgroup analysis showed that the addition of isoflavones did not decrease serum CRP and IL-6 levels; however a significant reduction of serum TNF-α was observed.…”
Section: Discussionsupporting
confidence: 93%
“…Findings from previous randomized controlled trials with soy foods and isoflavone supplements are inconsistent reporting increased [ 20 , 37 ], decreased [ 13 , 14 ], or no change [ 20 , 21 ] in concentrations of IL-6. Although soy food consumption was shown to inhibit IL-6 and TNF-α in a population study [ 10 ], results from recent meta-analyses and reviews of clinical trials examining the effect of soy intake on inflammation are inconclusive and show modest or no beneficial effects of soy intake in mitigating one or more of the cytokines or inflammatory indicators [ 38 , 39 , 40 ]. Although it is unclear why IL-6 levels increased in participants consuming the fermented soy powder, the causes may be due either to participant characteristics or the soy supplement dose.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that isoflavones as estrogens mimetics may exert pseudo-hormonal activity by binding to estrogen receptors in females [ 43 ]. Although some clinical trials of soy foods among women have shown reductions in TNF-α levels [ 12 , 17 ], findings from recent meta-analysis studies have been inconsistent [ 38 , 40 ]. One subgroup analysis of clinical trials reported that inhibition of TNF-α generally occurred in studies utilizing lower doses of isoflavones [ 31 ].…”
Section: Discussionmentioning
confidence: 99%